Ocean Acidification as Physical Indicator for Climate Change ... : تحمض المحيطات كمؤشر مادي لتغير المناخ ... - Mohammed Hussein Ba Naga (OpenAlex, 2022)
Atmospheric carbon dioxide concentration is expected to exceed 500 parts per million and global temperatures to rise by at least 2°C by 2050 to 2100, values that significantly exceed those of at least the past 420,000 years during which most extant marine organisms evolved. Under conditions expected in the 21st century, global warming and ocean acidification will be a greatly concerned. ... : من المتوقع أن يتجاوز تركيز ثاني أكسيد الكربون في الغلاف الجوي 500 جزء في المليون وأن ترتفع درجات الحرارة العالمية بمقدار درجتين مئويتين على الأقل بحلول عام 2050 إلى عام 2100، وهي قيم تتجاوز بشكل كبير تلك التي كانت على الأقل خلال الـ 420 ألف سنة الماضية التي تطورت خلالها معظم الكائنات البحرية الموجودة. في ظل الظروف المتوقعة في القرن الحادي والعشرين، سيكون الاحترار العالمي وتحمض المحيطات مصدر قلق كبير. ...